2008
DOI: 10.1088/0953-8984/20/23/235205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ru–Mn redox interactions on the hole carrier density in pulsed electron deposited La1−xPbxMn0.8Ru0.2O3(0.2≤x≤0.4) thin films

Abstract: Pulsed electron deposited thin films of Ru substituted La(1-x)Pb(x)Mn(0.8)Ru(0.2)O(3) (0.2≤x≤0.4) show an increase in the magneto-resistance ratio by ∼5-15% at the respective metal to insulator transition (T(MIT)) temperature when compared to the parent La(0.6)Pb(0.4)MnO(3) thin film. A systematic decrease in T(MIT) is observed from ∼310 to ∼260 K when the hole (Pb) concentration varies from 40 to 20% with constant 20% Ru substitution at the Mn site. The x-ray rocking curve and high-resolution transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…T MIT and T c may have originated predominantly from the chemical pressure effects of the cationic size of the Ca ion, deficiency of the hole carrier density that brings in charge carrier localization due to the random magnetic potential effects, as was demonstrated for the Ru substituted samples. 35,36 Fig. 3(i and ii) and 4(i and ii) show the impedance and magneto impedance of La 0.7 Ca 0.3 Mn 1Àx Ru x O 3 (0 r x r 0.3) thin films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T MIT and T c may have originated predominantly from the chemical pressure effects of the cationic size of the Ca ion, deficiency of the hole carrier density that brings in charge carrier localization due to the random magnetic potential effects, as was demonstrated for the Ru substituted samples. 35,36 Fig. 3(i and ii) and 4(i and ii) show the impedance and magneto impedance of La 0.7 Ca 0.3 Mn 1Àx Ru x O 3 (0 r x r 0.3) thin films.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that in Ru substituted manganite, wherein the Ru concentration was 420%, those compositions showed a charge carrier localization effect. 35,36 This effect arises because (i) hole carrier density being decreased due to the Ru 4+ (ii) in the presence of the Ru 4+ valence state, the e g electron is not able to hop from Mn 3+ . In Fig.…”
Section: Resultsmentioning
confidence: 99%